Adler function, Bjorken polarized sum rule: confirmation of elements of the β-expansion and the diagrams - S. V. Mikhailov (Journal of High Energy Physics)
Abstract Different ways exist to obtain the elements of the β-expansion for renormgroup invariant quantities. Here we consider independent confirmation within the standard QCD of a number of our results [1] for the values of elements of this expansion for the nonsinglet Adler D A -function, Bjorken polarized sum rules S Bjp up to the order N4LO. We suggest an approach to estimate the results of high order QCD calculations using a smaller number of diagrams of the specific type. This type is based on a proposed generalization of Naive NonAbelianization.